Optimizing Community-Based Healthcare Facility Image to Enhance Patient Interest and Trust in Inpatient Services - Martianawati; sugiyono; qoyimah, ilmiatus (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program was carried out to strengthen the public image of healthcare facilities and enhance trust in inpatient service utilization in Sidoarjo Regency. The initiative employed a community-based participatory approach involving residents, health cadres, community organizations, and healthcare providers. Through educational workshops, focus group discussions, interactive forums, and the dissemination of health information materials, the program successfully improved community understanding of inpatient service standards and addressed misconceptions that previously contributed to hesitancy in seeking care. The results demonstrated increased health literacy, strengthened community–provider communication, and improved public perception of the healthcare facility's credibility. Collaboration between healthcare workers and community groups was notably enhanced, enabling sustained dissemination of accurate health information. Although long-term impacts on inpatient utilization require continued monitoring, the program effectively established a foundation for increased public trust and more informed health-seeking behavior. These findings underscore the importance of transparent communication, community engagement, and sustained partnerships in enhancing healthcare service utilization at the local level.